2022
DOI: 10.1038/s41598-022-11236-2
|View full text |Cite
|
Sign up to set email alerts
|

Metformin combined with local irradiation provokes abscopal effects in a murine rectal cancer model

Abstract: Although preoperative chemoradiation therapy can down-stage locally advanced rectal cancer (LARC), it has little effect on distant metastases. Metformin exerts an anti-cancer effect partly through the activation of host immunity. LuM1, a highly lung metastatic subclone of colon 26, was injected subcutaneously (sc) in BALB/c mice and treated with metformin and/or local radiation (RT). Lung metastases and the primary tumors were evaluated and the phenotypes of immune cells in the spleen and lung metastases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Additionally, metformin seems to selectively kill cancer stem cells, which are the most radioresistant type of tumor cells [101]. Subsequently, the drug also alters the immune status [103]. Additionally, metformin has been linked to the induction of ferroptosis by modulation of several pathways, such as SLC7A11, GPX4, iron metabolism, etc., in breast cancer (Figure 2).…”
Section: Metforminmentioning
confidence: 99%
“…Additionally, metformin seems to selectively kill cancer stem cells, which are the most radioresistant type of tumor cells [101]. Subsequently, the drug also alters the immune status [103]. Additionally, metformin has been linked to the induction of ferroptosis by modulation of several pathways, such as SLC7A11, GPX4, iron metabolism, etc., in breast cancer (Figure 2).…”
Section: Metforminmentioning
confidence: 99%
“…In another study, the combination of RT and 2‐hexyl‐4‐pentylenic acid (HPTA), a valproic acid derivative, demonstrated a significant abscopal effect by M1 polarization of tumor‐associated macrophages in a breast cancer model, implying that HPTA could be used as a novel neoadjuvant to stimulate RT‐induced abscopal effect in the treatment of breast cancer [ 101 ]. A study reported that the combination of metformin and RT suppressed the growth of nonirradiated lung metastasis in a murine rectal cancer model [ 102 ]. The combination of PI3K/inhibitor (BR101801) and XRT in the CT‐26 syngenic mouse model demonstrated an abscopal effect by increasing the cytotoxic T‐cell to T‐reg cell ratio, insinuating that the combined therapy of PI3K/inhibitor and RT converts immunologically cold tumors into immunologically hot tumors [ 103 ].…”
Section: Challenges In Producing the Abscopal Effect And Overcoming Themmentioning
confidence: 99%
“…The activation of NK cells was mediated by the activation of p38 mitogen-activated protein kinases (MAPK), which has cytolytic granules secreting ability [37]. Additionally, metformin combined with local radiation therapy markedly increased NKp46/CD335 + NK cells in the metastatic tumors in a metastatic mouse lung model [57]. In the clinical trial of HNSCC patients, pretreatment of patients with metformin has been shown to significantly increase the presence of NKp46 + cells in the tumor tissue.…”
Section: Effect Of Metformin On Nk Cellsmentioning
confidence: 99%